2011
DOI: 10.1016/j.jamcollsurg.2011.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effective Treatment of Patients with Symptomatic Cholelithiasis and Possible Common Bile Duct Stones

Abstract: Background Clinicians must choose a treatment strategy for patients with symptomatic cholelithiasis without knowing whether common bile duct (CBD) stones are present. The purpose of this study was to determine the most cost-effective treatment strategy for patients with symptomatic cholelithiasis and possible CBD stones. Study Design Our decision model included five treatment strategies: (1) laparoscopic cholecystectomy (LC) alone followed by expectant management, (2) preoperative endoscopic retrograde chola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
12

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 57 publications
(68 reference statements)
0
24
0
12
Order By: Relevance
“…When repeat cholangiogram and ERCP were performed at six weeks, nearly three out of four of patients had persistent choledocholithiasis (9). Several authors have reported that about 5–15% of patients undergoing laparoscopic cholecystectomy for uncomplicated symptomatic cholecystitis have common bile duct stones (1214). …”
Section: Discussionmentioning
confidence: 99%
“…When repeat cholangiogram and ERCP were performed at six weeks, nearly three out of four of patients had persistent choledocholithiasis (9). Several authors have reported that about 5–15% of patients undergoing laparoscopic cholecystectomy for uncomplicated symptomatic cholecystitis have common bile duct stones (1214). …”
Section: Discussionmentioning
confidence: 99%
“…In addition, Ammori et al [22] proposed that a "wait and see" policy of observation alone for patients with small bile duct calculi detected at intraoperative cholangiography (IOC) during laparoscopic cholecystectomy appears to be safe, and is more cost-effective than routine postoperative ERCP. Furthermore, some studies have suggested that the most cost-effective treatment strategy for most patients with symptomatic cholelithiasis involves laparoscopic cholecystectomy with routine IOC, as IOC can help laparoscopists to visualize the biliary anatomy and detect unexpected CBD stones [2324]. However, it remains debated whether IOC provides sufficient benefits in terms of its efficacy and safety to justify its routine application.…”
Section: Discussionmentioning
confidence: 99%
“…Previous decision analyses have dealt mostly with the management of CBD stones, including cholecystectomy and intraoperative CBD exploration [11][12][13][14]. In contradistinction, the present analysis is restricted to the preoperative work-up by radiologic and endoscopic imaging techniques.…”
Section: Discussionmentioning
confidence: 99%